Diagnostic difficulties in progressive multifocal leukoencephalopathy: a case report - Stapińska-Syniec, Angelika; Sobstyl, Michał; Kurowska, Katarzyna; Acewicz, Albert; Wierzba-Bobrowicz, Teresa (Folia Neuropathologica, 2025)
Progressive multifocal leukoencephalopathy (PML) is a demyelination disease of the central nervous system (CNS) caused by viral infection with John Cunningham polyomavirus (JC virus, JCV). PML affects mainly patients with immunodeficiency. Since the diagnosis is often challenging, it requires the close cooperation of clinicians. Due to the lack of specific treatment of JCV infection leading to PML, the current treatment is based on reversing the immunosuppression. Here we present a case of a 58-year-old woman who was ultimately diagnosed with PML based on neuropathological analysis of stereotactic biopsy specimens